Normal variation of the gut microbiota affects hepatic cytochrome P450 activity in mice - Masao Togao; Shinnosuke Tajima; Takashi Kurakawa; Gaku Wagai; Jun Otsuka; Shoichi Kado; Koji Kawakami (Wiley, 2021)
Abstract Several studies revealed that substantial artificial changes in the gut microbiota resulted in modification of hepatic cytochrome P450 3a (Cyp3a) in mice. Consequently, we hypothesized that "normal" variation of the gut microbiota might also alter hepatic Cyp activity and lead to individual differences in drug metabolism. Therefore, this study investigated the effects of normal gut microbiota variation on hepatic Cyp activity under the same genetic and environmental conditions using ex‐germ‐free mice. Using the feces of three breeder BALB/c mice (Jcl, Slc, and Crj), germ‐free BALB/cYit mice were conventionalized (Yit‐Jcl, Yit‐Slc, and Yit‐Crj). The gut microbiota composition and hepatic Cyp activity of these donors and recipients were evaluated. 16S rRNA sequencing revealed clear differences of the gut microbiota among donors and among recipients. Cyp3a activity was significantly higher in Slc mice than in Jcl and Crj mice. Notably, among recipients, Cyp3a activity was significantly higher in Yit‐Slc and Yit‐Crj mice than in Yit‐Jcl mice. Cyp2b activity was significantly higher in Slc mice than in Jcl and Crj mice. Cyp2b activity was significantly higher in Yit‐Slc mice than in Yit‐Jcl mice. Additionally, in correlation analysis, some genera displayed significant positive or negative correlations with Cyp activity, particular the strong positive correlation between Clostridium sensu stricto 1 with Cyp3a activity. In conclusion, this study demonstrated that normal variation of the gut microbiota affected hepatic Cyp3a and Cyp2b activity, which might result in individual differences of drug metabolism.